Cybercrime Strategy: The Ideal vs. the Reality - P. A. Skoblikov (Сибирское юридическое обозрение)
The author draws attention to the fact that, for various reasons, law enforcement agencies are not sufficiently focused on the timely and thorough detection of crimes committed using information and communication technologies or within the sphere of computer data. Reports of such crimes are often not pursued immediately, and in many cases are only addressed long after being filed – typically by personnel who lack the necessary skills, forensic tools, operational-search capacities, and procedural authority. If the victim has not suffered material damage or if the damage is relatively minor, refusals to initiate criminal proceedings are often issued on questionable grounds. The article presents and substantiates the hypothesis that the actual scale of cybercrime is many times greater than what is officially recorded. As a result, the stakeholders in criminal policy lack an accurate understanding of the situation in this area of crime control. The author emphasizes that in the face of such an information deficit, it is impossible to make informed managerial decisions regarding the optimal allocation of existing resources, the need for and extent of reinforcement, existing organizational and legal shortcomings, or effective strategies for improvement. This problematic situation is rooted in the fact that essential principles are neither established in criminal-policy documents nor reflected in real-world criminal policy. Current policy encourages law enforcement to present a distorted but tolerable picture of criminological conditions, rather than confront the unfavorable realities on the ground. The article concludes by articulating key principles for an effective cybercrime strategy – principles that must be formally outlined at the conceptual level and consistently implemented in practice.